SYNTHESIS & EVALUATION OF AN ENVIRONMENTAL FRIENDLY OIL BASED EMULSIFIED ACID FOR CARBONATE MATRIX ACIDIZING - YOUSUFI, MUHAMMAD MOHSIN (2018)
Matrix acidizing operations have been accounted to be the most hazardous and environmentally harmful among all the well stimulation techniques. In instance, diesel oil based emulsified acids have been prohibited from usage due to their high level of toxicity in the US Policy Act of 2005